Sub-Nano Pt/β-FeOOH Quantum Dots for Photocatalytic Removal of Toluene: Catalyst Design, Preparation, and Benefits - Pei, Mengxi; Lv, Shangchun; Liu, Yishui; Si, Zhichun; Wu, Xiaodong; Ran, Rui; Weng, Duan; Kang, Feiyu (Frontiers in Materials, 2022)
Photocatalytic removal of organic pollutants under solar irradiation at room temperature is considered as an energy-saving technic of environmental remediation. However, the photocatalysis is impeded by the poor response to visible light and fast charge recombination. In this work, sub-nano Pt/-FeOOH Quantum Dot (QD) was designed to shorten the charge migration path and obtain wide light harvesting. Interestingly, the crystalline -FeOOH QDs can be obtained by loading sub-nano Pt particles via a reconstruction mechanism of amorphous FeOOH induced by H2 spillover, which facilitates the fast kinetics of charge transition and benefits the oxygen-rich surface of catalyst for photocatalytic oxidation reactions. Moreover, the Pt-VO-Fe interfaces were proved to be the most active sites for the activation of O2. As a result, the catalyst exhibits a predominant photocatalytic performance in toluene oxidation, achieving TOFPt of 0.591 min-1 at room temperature under visible light irradiation. This work provides a new perspective on the design and preparation of nanocatalysts for high efficient photocatalysis under visible light irradiation.